Apprenticeship: A method to develop competencies in a top level sport team - Ronglan, L. T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The study revealed that apprenticeship was used as a central learning strategy in the group, especially in relation to technical development. Players in the same playing position on the field was put together in parts of the training session (3 left wings, 3 centers etc.), to coach each other and develop the specific position skills. Often the players were position experts (Dreyfus & Dreyfus 1986) with different personal qualities, and each of them could pick up ideas by observerving/beeing observed and coching/beeing coached by their teammates. Rather than instruction-based strategies, this player-player strategy dominated the technical training in the team. Genuin practical knowledge, such as skills in sport, can not fully be catched by verbal instruction. To a large extent this kind of knowledge is tacid (Polanyi 1966) Apprenticeship was used as a strategy to utilize the embodied competencies among the expert players.